Cadmium, copper, and chromium levels in maize plants and soil fertilized with sewage sludge - Reis, Iolanda Maria Soares; Alves, Suelen Cristina Nunes [UNESP]; de Melo, Wanderley José [UNESP]; Silva, Laércio Santos [UNESP]; de Freitas, Ludmila; de Oliveira, Ivanildo Amorim; Barros, Ianna Bizerra; de Melo, Gabriel Maurício Peruca; de Melo, Valéria Peruca (Southern Cross Publishing, 2020)
The use of sewage sludge as fertilizer is a widespread practice. However, the presence of heavy metals and pathogens in sludge are a cause for concern. The objective of this study was to determine the levels of cadmium (Cd), copper (Cu), and chromium (Cr) in leaves, aerial parts, and kernels of maize grown in red latosol that was fertilized with sewage sludge for 15 consecutive years. Metal concentrations in soil and kernel yield were also determined. A randomized block design was used, with five replicates and four treatments: T1, mineral fertilization (control); T2, application of sewage sludge at 5 Mg ha−1; T3, application of sewage sludge at 10 Mg ha−1; and T4, application of sewage sludge at 20 Mg ha−1. All plots received potassium (K) supplementation. Fertilization with sewage sludge was as efficient as mineral fertilization. Sewage sludge had no negative effect on kernel yield. A negative correlation was observed between metal concentrations in soil and plant samples. Cd was detected at ≤0.04 mg kg−1 in kernels and Cu at ≤2.34 mg kg−1, whereas Cr was not detected in any sample. These levels are considered safe for human consumption, according to the Brazilian Health Regulatory Agency. Fertilization with sewage sludge for 15 years did not increase Cu, Cd, and Cr levels in the soil and had no negative effect on maize, which shows the potential of sewage sludge for agricultural use.
Keywords: Bioaccumulation; Heavy metal; Pollution; Productivity; Soil science